Answer:
![y = \frac{7}{10} e^{3(t - 1)} + \frac{3}{10}e^{-7(t - 1)}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B7%7D%7B10%7D%20e%5E%7B3%28t%20-%201%29%7D%20%2B%20%5Cfrac%7B3%7D%7B10%7De%5E%7B-7%28t%20-%201%29%7D)
Step-by-step explanation:
y′′ + 4y′ − 21y = 0
The auxiliary equation is given by
m² + 4m - 21 = 0
We solve this using the quadratic formula. So
![m = \frac{-4 +/- \sqrt{4^{2} - 4 X 1 X (-21))} }{2 X 1}\\ = \frac{-4 +/- \sqrt{16 + 84} }{2}\\= \frac{-4 +/- \sqrt{100} }{2}\\= \frac{-4 +/- 10 }{2}\\= -2 +/- 5\\= -2 + 5 or -2 -5\\= 3 or -7](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-4%20%2B%2F-%20%5Csqrt%7B4%5E%7B2%7D%20-%204%20X%201%20X%20%28-21%29%29%7D%20%7D%7B2%20X%201%7D%5C%5C%20%3D%20%5Cfrac%7B-4%20%2B%2F-%20%5Csqrt%7B16%20%2B%2084%7D%20%7D%7B2%7D%5C%5C%3D%20%5Cfrac%7B-4%20%2B%2F-%20%5Csqrt%7B100%7D%20%7D%7B2%7D%5C%5C%3D%20%5Cfrac%7B-4%20%2B%2F-%2010%20%7D%7B2%7D%5C%5C%3D%20-2%20%2B%2F-%205%5C%5C%3D%20-2%20%2B%205%20or%20-2%20-5%5C%5C%3D%203%20or%20-7)
So, the solution of the equation is
![y = Ae^{m_{1} t} + Be^{m_{2} t}](https://tex.z-dn.net/?f=y%20%3D%20Ae%5E%7Bm_%7B1%7D%20t%7D%20%2B%20Be%5E%7Bm_%7B2%7D%20t%7D)
where m₁ = 3 and m₂ = -7.
So,
![y = Ae^{3t} + Be^{-7t}](https://tex.z-dn.net/?f=y%20%3D%20Ae%5E%7B3t%7D%20%2B%20Be%5E%7B-7t%7D)
Also,
![y' = 3Ae^{3t} - 7e^{-7t}](https://tex.z-dn.net/?f=y%27%20%3D%203Ae%5E%7B3t%7D%20-%207e%5E%7B-7t%7D)
Since y(1) = 1 and y'(1) = 0, we substitute them into the equations above. So,
![y(1) = Ae^{3X1} + Be^{-7X1}\\1 = Ae^{3} + Be^{-7}\\Ae^{3} + Be^{-7} = 1 (1)](https://tex.z-dn.net/?f=y%281%29%20%3D%20Ae%5E%7B3X1%7D%20%2B%20Be%5E%7B-7X1%7D%5C%5C1%20%3D%20Ae%5E%7B3%7D%20%2B%20Be%5E%7B-7%7D%5C%5CAe%5E%7B3%7D%20%2B%20Be%5E%7B-7%7D%20%3D%201%20%20%20%20%20%20%281%29)
![y'(1) = 3Ae^{3X1} - 7Be^{-7X1}\\0 = 3Ae^{3} - 7Be^{-7}\\3Ae^{3} - 7Be^{-7} = 0 \\3Ae^{3} = 7Be^{-7}\\A = \frac{7}{3} Be^{-10}](https://tex.z-dn.net/?f=y%27%281%29%20%3D%203Ae%5E%7B3X1%7D%20-%207Be%5E%7B-7X1%7D%5C%5C0%20%3D%203Ae%5E%7B3%7D%20-%207Be%5E%7B-7%7D%5C%5C3Ae%5E%7B3%7D%20-%207Be%5E%7B-7%7D%20%3D%200%20%5C%5C3Ae%5E%7B3%7D%20%3D%207Be%5E%7B-7%7D%5C%5CA%20%3D%20%5Cfrac%7B7%7D%7B3%7D%20Be%5E%7B-10%7D)
Substituting A into (1) above, we have
![\frac{7}{3}B e^{-10}e^{3} + Be^{-7} = 1 \\\frac{7}{3}B e^{-7} + Be^{-7} = 1\\\frac{10}{3}B e^{-7} = 1\\B = \frac{3}{10} e^{7}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B3%7DB%20e%5E%7B-10%7De%5E%7B3%7D%20%2B%20Be%5E%7B-7%7D%20%3D%201%20%20%20%20%20%20%5C%5C%5Cfrac%7B7%7D%7B3%7DB%20e%5E%7B-7%7D%20%2B%20Be%5E%7B-7%7D%20%3D%201%5C%5C%5Cfrac%7B10%7D%7B3%7DB%20e%5E%7B-7%7D%20%3D%201%5C%5CB%20%3D%20%5Cfrac%7B3%7D%7B10%7D%20e%5E%7B7%7D)
Substituting B into A, we have
![A = \frac{7}{3} \frac{3}{10} e^{7}e^{-10}\\A = \frac{7}{10} e^{-3}](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B7%7D%7B3%7D%20%5Cfrac%7B3%7D%7B10%7D%20e%5E%7B7%7De%5E%7B-10%7D%5C%5CA%20%3D%20%5Cfrac%7B7%7D%7B10%7D%20e%5E%7B-3%7D)
Substituting A and B into y, we have
![y = Ae^{3t} + Be^{-7t}\\y = \frac{7}{10} e^{-3}e^{3t} + \frac{3}{10} e^{7}e^{-7t}\\y = \frac{7}{10} e^{3(t - 1)} + \frac{3}{10}e^{-7(t - 1)}](https://tex.z-dn.net/?f=y%20%3D%20Ae%5E%7B3t%7D%20%2B%20Be%5E%7B-7t%7D%5C%5Cy%20%3D%20%5Cfrac%7B7%7D%7B10%7D%20e%5E%7B-3%7De%5E%7B3t%7D%20%2B%20%5Cfrac%7B3%7D%7B10%7D%20e%5E%7B7%7De%5E%7B-7t%7D%5C%5Cy%20%3D%20%5Cfrac%7B7%7D%7B10%7D%20e%5E%7B3%28t%20-%201%29%7D%20%2B%20%5Cfrac%7B3%7D%7B10%7De%5E%7B-7%28t%20-%201%29%7D)
So the solution to the differential equation is
![y = \frac{7}{10} e^{3(t - 1)} + \frac{3}{10}e^{-7(t - 1)}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B7%7D%7B10%7D%20e%5E%7B3%28t%20-%201%29%7D%20%2B%20%5Cfrac%7B3%7D%7B10%7De%5E%7B-7%28t%20-%201%29%7D)